Upaya Peningkatan Kandungan Teknologi Berdasarkan Hasil Pengukuran Aspek Teknologi Menggunakan Pendekatan Teknometrik - Aulian, M Hannas, Much Djunaidi, ST, MT (2016)
The incredible potential that results from making rattan livelihood for the villagers of Trangsan, sub Gatak, Sukoharjo to serve as furniture, but some of the rattan industry has not noticed aspects of the technology applied in industry. The purpose of this study was to determine the levels of the technology applied by the cane industry CV Sumber Jaya and Tina Rattan, then make a proposal to Tina Rattan cane industry, based on the value of the lowest contribution of technology components. CV Sumber Jaya and Tina Rattan are two of the many rattan industry in the village Trangsan, CV Sumber Jaya is the export of rattan industry, while Tina Rattan is a local marketing rattan industry. Technometric method is a method used to determine the classification of the technology by dividing them into four components, technoware, humanware, infoware, and organware an integrated, which will then be generated value of TCC (Technology Contribution Coefficient) used to determine the level of technology applied. Based on the results of research on the CV Sumber Jaya is contribution of the four components of the technology are technoware of 0.52, humanware amounted to 0.67, infoware of 0.43, organware of 0.63 which means that the classification of technologies that are in reasonable limits, while in Tina Rattan, technoware of 0.32, humanware of 0.42, infoware of 0.25, organware of 0.47, which means classification technology is at the lower end, the results of the value of the lowest contribution to Tina Rattan is infoware. Keywords: creative industries, rattan, TCC, technometric, Trangsan.